The Effect of Pellet Mill Production Rate and Knife Distance on Pellet Quality - C. E. Evans; R. J. Beeman; M. Saensukjaroenphon; C. B. Paulk; C. R. Stark (Kansas Agricultural Experiment Station Research Reports, 2019)
Longer pellet lengths may lead to decreased pellet breakage, resulting in increased pellet durability index (PDI). Thus, the objective of this experiment was to determine the effects of production rate and knife distance on pellet length and subsequent pellet quality. Treatments were arranged in a 2 × 3 factorial with two production rates (16 and 33 lb/min) and three knife distances (0.25, 0.50, and 0.75 in). All diets were conditioned at 185°F and pelleted using a CPM pellet mill (Model 1012-2 HD, California Pellet Mill Co., Crawfordsville, IN) equipped with a 0.19 in × 1.25 in die. The production rate (PR) and knife distance (KD) were randomized to minimize the effects of pelleting and sampling order. There were 3 replicates per treatment. Samples were analyzed for pellet length, percentage fines, and PDI using the standard and modified tumble box method (STD and MOD, respectively) and Holmen NHP100 (TekPro Ltd, Norfolk, UK) with a 60-sec run time. Data were analyzed using the GLIMMIX procedure of SAS (v. 9.4, SAS Inst. Inc., Cary, NC). There was no evidence for an interaction between PR and KD for all analyzed variables (P>0.24). The 16 lb/min PR yielded a longer pellet (P ≤0.05) compared to the 33 lb/min PR. The PR had no effect on percentage fines (P>0.10); however, decreasing the PR tended to increase PDI regardless of analytical method (P≤ 0.10). Increasing KD resulted in longer (P<0.01) pellets and decreased (P<0.01) percentage fines. Reducing KD to 0.25 in reduced PDI compared to 0.50 in and 0.75 in treatments, which yielded similar PDI. In conclusion, pellet quality can be improved by increasing the pellet length from 0.19 to 0.34 in (KD 0.25 and 0.75 in, respectively).
Keywords: pellet quality; pellet length; knife distance; production rate